Epsin3 promotes non-small cell lung cancer progression via modulating EGFR stability - Huiling Su; Jie Shen; Chenzi Gao; Yue Zhao; Wanyu Deng; Bo Qin; Xin Zhang; Juan Lai; Qian Wang; Jie Dou; Min Guo (Cell & Bioscience)
Abstract Background The abnormal expression and overactivation of the epidermal growth factor receptor (EGFR), a typical cancer marker for non-small cell lung cancer (NSCLC), are closely related to the tumorigenesis and progression of NSCLC. However, the endocytosis mechanism of EGFR in lung cancer is not yet known. Epsin3 (EPN3), a member of the endocytic adaptor protein family, is essential for the endocytosis of multiple receptors. In this study, we aimed to investigate the role of EPN3 in modulating EGFR function, its effects on NSCLC progression, and its potential involvement in tyrosine kinase inhibitor (TKI) resistance, which remains a significant hurdle in NSCLC treatment. Results Our findings revealed that the expression of EPN3 is significantly up-regulated in NSCLC patients. Elevated EPN3 expression was proportional to shorter overall survival in patients with NSCLC. Functional analyses revealed that EPN3 directly interacts with EGFR, enhancing its recycling to the plasma membrane and preventing its degradation via the lysosomal pathway. This stabilization of EGFR led to sustained downstream signalling, promoting NSCLC cell proliferation and migration. Notably, mutations in the EGFR tyrosine kinase domain, which typically confer resistance to TKIs, did not alter the regulatory effect of EPN3. Conclusions EPN3 enhances EGFR signalling by promoting its recycling and stability, contributing to NSCLC progression and TKI resistance. Targeting EPN3 could offer a novel therapeutic strategy to overcome drug resistance in EGFR-driven NSCLC.